2022
DOI: 10.3390/children9121891
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Junk Food Consumption with Preadolescents’ Environmental Influences: A School-Based Epidemiological Study in Greece

Abstract: The aim of the present study was to evaluate the impact of environmental influences on Greek preadolescents’ junk food consumption. A cross-sectional study, was conducted among 1718 preadolescents (mean (standard deviation(SD)) age: 11.2(0.8) years old; 54% girls) and their parents, during the school years 2014–2016. Parental and child characteristics were collected anonymously, through self-administered and validated questionnaires. Among others, junk food consumption was recorded, classifying children as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A socio-ecological approach [ 42 ] can identify factors that could be addressed by interventions at maternal–child, family, community, and global levels. At the maternal–child level, the correlations between childhood UPF/SSB consumption with both mother’s UPF/SSB consumption and children’s age [ 43 , 44 ] demonstrate that prenatal, postpartum and early childhood maternal–child health services should educate on the short- and long-term health hazards of eating non-nutritious snack foods and drinking sugary beverages. In the informal settlement communities included in our sample, we found that higher maternal education was associated with lower child UPF/SSB consumption, which is consistent with other studies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A socio-ecological approach [ 42 ] can identify factors that could be addressed by interventions at maternal–child, family, community, and global levels. At the maternal–child level, the correlations between childhood UPF/SSB consumption with both mother’s UPF/SSB consumption and children’s age [ 43 , 44 ] demonstrate that prenatal, postpartum and early childhood maternal–child health services should educate on the short- and long-term health hazards of eating non-nutritious snack foods and drinking sugary beverages. In the informal settlement communities included in our sample, we found that higher maternal education was associated with lower child UPF/SSB consumption, which is consistent with other studies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that salty taste is a steadily learned preference, the recommendation regarding the limitation of salt intake in adulthood would be more easily met should this habit start earlier in life [40]. Unfortunately, however, literature largely agrees that at preadolescence, children tend to increase their junk food consumption, leading to higher amounts of sodium consumed that could have a detrimental impact on their general eating habits long-term [41]. Current daily salt consumption in most European countries is estimated to be, on average, twice as high as the recommended daily consumption for children and adults, with processed foods being the major source [42].…”
Section: Micronutrients In Diatrofi Mealsmentioning
confidence: 99%
“…Therefore, the World Health Organization (WHO) has called for restrictions on the marketing of certain products, such as tobacco products and unhealthy foods/drinks to children and young adolescents [ 7 ]. Junk food advertisements have been described as a detrimental factor shaping junk food consumption in adolescents, along with interactions with environmental factors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%